Dorsal hippocampus plays a causal role in context-induced reinstatement of alcohol-seeking in rats - Felipe, Jaqueline Moreira; Palombo, Paola; Bianchi, Paula Cristina; Zaniboni, Caroline Riberti; Anésio, Augusto; Yokoyama, Thais Suemi; Engi, Sheila Antonagi; Carneiro-de-Oliveira, Paulo Eduardo; Planeta, Cleopatra da Silva [UNESP]; Leão, Rodrigo Molini; Cruz, Fábio Cardoso (Elsevier, 2021)
Drug addiction is a chronic mental disorder characterized by frequent relapses. Contextual cues associated with drug use to play a critical causal role in drug-seeking behavior. The hippocampus has been implicated in encoding drug associative memories. Here we examine whether the dorsal hippocampus mediates context-induced reinstatement of alcohol-seeking. Male Long-Evans rats were trained to self-administer alcohol in Context A. Alcohol self-administration was extinguished in a distinct context (Context B). On the test day, animals were re-exposed to the alcohol Context A or the extinction Context B. Next, to assess a causal role for the dorsal hippocampus in context-induced alcohol-seeking, on the test day, we injected cobalt chloride (CoCl2; a nonselective synapse inhibitor) or vehicle into the dorsal hippocampus, and 15 min later, rats were tested by re-exposing them to the drug-associated context. The re-exposure to the alcohol-associated Context A reinstated alcohol seeking and increased Fos-positive cells in the dorsal hippocampus neurons (CA1, CA3, and Dentate Gyrus). Pharmacological inactivation with cobalt chloride of the dorsal hippocampus attenuated the reinstatement of alcohol-seeking. Our data suggest that the dorsal hippocampus may be involved in context-induced alcohol-seeking behavior.
Keywords: Alcohol self-administration; Drug environment; Extinction; Reinstatement